Utility of PTEN and ERG Immunostaining for Distinguishing High-grade PIN From Intraductal Carcinoma of the Prostate on Needle Biopsy. (February 2015) - Morais, Carlos L.; Han, Jeong S.; Gordetsky, Jennifer; Nagar, Michael S.; Anderson, Ann E.; Lee, Stephen; Hicks, Jessica L.; Zhou, Ming; Magi-Galluzzi, Cristina; Shah, Rajal B.; Epstein, Jonathan I.; De Marzo, Angelo M.; et al.
Abstract : Intraductal carcinoma of the prostate and high-grade prostatic intraepithelial neoplasia (PIN) have markedly different implications for patient care but can be difficult to distinguish in needle biopsies. In radical prostatectomies, we demonstrated that PTEN and ERG immunostaining may be helpful to resolve this differential diagnosis. Here, we tested whether these markers are diagnostically useful in the needle biopsy setting. Separate or combined immunostains were applied to biopsies containing morphologically identified intraductal carcinoma, PIN, or borderline intraductal proliferations more concerning than PIN but falling short of morphologic criteria for intraductal carcinoma. Intraductal carcinoma occurring with concurrent invasive tumor showed the highest rate of PTEN loss, with 76% (38/50) lacking PTEN and 58% (29/50) expressing ERG. Of biopsies containing isolated intraductal carcinoma, 61% (20/33) showed PTEN loss and 30% (10/33) expressed ERG. Of the borderline intraductal proliferations, 52% (11/21) showed PTEN loss and 27% (4/15) expressed ERG. Of the borderline cases with PTEN loss, 64% (7/11) had carcinoma in a subsequent needle biopsy specimen, compared with 50% (5/10) of PTEN-intact cases. In contrast, none of the PIN cases showed PTEN loss or ERG expression (0/19). On needle biopsy, PTEN loss is common in morphologically identified intraductal carcinoma yet is very rare in high-grade PIN. Borderline intraductal proliferations, especially those with PTEN loss, have a high rate of carcinoma on resampling. If confirmed in larger prospective studies, these results suggest that PTEN and ERG immunostaining may provide a useful ancillary assay to distinguish intraductal carcinoma from high-grade PIN in this setting.